SADEMIN: Sistem Cerdas Deteksi Kelayakan Makanan dan Minuman Berbasis Sensor Gas dan Internet of Things (IoT) - Muhammad Zikry Al-Banna Lubis; Sukarman Purba; Tora Valentina Simatupang; Andri Saputra Harahap (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2026)
Food safety is a fundamental aspect of public health; however, the rate of food poisoning in Indonesia remains alarmingly high, with reports indicating 4,711 cases by September 2025. This issue is compounded by the limitations of traditional methods that are subjective and the inability to detect food spoilage in its early stages, during which microorganisms start to emit Volatile Organic Compounds (VOCs) like ammonia and alcohol vapors that human senses cannot identify. The aim of this innovative concept is to create SADEMIN (Smart Food and Beverage Eligibility Detection System) as an intelligent detection system based on the Internet of Things (IoT) for objectively, accurately, and continuously monitoring food freshness. SADEMIN is engineered by incorporating MQ-135 gas sensors and MQ-3 alcohol sensors controlled by the ESP8266 microcontroller. This innovation operates by identifying gas emissions of ammonia and ethanol resulting from food degradation, assigning a